KOLABORASI ETIS GURU PENDIDIKAN AGAMA ISLAM DALAM MENGHADAPI KRISIS MORAL DI ERA DIGITAL - Halul Aliyah; Muhammad Fadlan Ramadhan; Muhamad Rizqi Zidan; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the concept of ethical collaboration among Islamic Religious Education (PAI) teachers as a strategy for strengthening moral education in the digital era. The increasing cases of cyberbullying, hate speech, hoax dissemination, and the degradation of digital communication ethics indicate that moral education can no longer rely solely on individual approaches. This study employed a qualitative approach using the library research method through stages of identification, selection, critical evaluation, and thematic synthesis of various national and international scientific literatures. The data sources were obtained from indexed scientific articles, academic books, and reports from international institutions published between 2022 and 2026 related to digital ethics, moral education, collaborative learning, and Islamic education. A total of 32 articles were analyzed using thematic analysis techniques. The findings reveal that ethical collaboration is not merely interpreted as professional cooperation among teachers, but also as a collective moral practice built upon the values of trustworthiness (amanah), responsibility, dialogical communication, and respect for differences in digital spaces. The implementation of ethical collaboration is reflected through professional learning communities, the strengthening of Islamic values-based digital literacy, ethical communication, and collaborative school leadership. This study contributes theoretically to the development of the concept of ethical collaboration as an Islamic moral education framework that is adaptive to the challenges of digital transformation.